Selected aspects of the marketing of bus transport companies during COVID-19 - Eva Kicova; Olga Ponisciakova; Zuzana Rosnerova (Business: Theory and Practice, 2023)
The COVID-19 pandemic has caused a significant worldwide decrease in the number of passengers using bus transport in recent years. This phenomenon was caused by travelers’ fears of this disease, and at the same time, people started working from home. The aim of the paper is to analyze the importance of marketing and marketing strategies for bus companies. From our point of view, marketing is a tool for making bus transport more attractive for passengers. For the purposes of this post, we focus on customer perceptions of marketing and marketing strategies. We found that customers prefer Internet advertising the most, and the second most preferred type of advertising is print advertising. Their proposals in the subject area are also based on other findings that we dealt with in the survey. We investigated the motivation of passengers to use public transport, their opinion about the transport company in the Zilina region, and whether they use modern tools such as e-shops, virtual cards, and similar. As part of the papers processing, we used the questionnaire survey method, conducted a statistical evaluation of established hypotheses, and conducted a structured interview with the management of the bus company. From our point of view, it is marketing based on managerial experience and customer preferences that can be beneficial for the overall attractiveness of bus transport and, at the same time, significantly contribute to increasing the competitiveness of these businesses.